Profit Sharing and Relative Consumption - Laszlo Goerke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
Traditionally, it has been argued that profit sharing can increase employment and welfare because it lowers marginal labour costs without reducing labour income. In this paper, we show that profit sharing can also represent a Pareto-improvement if labour supply is excessive due to relative consumption effects. This is the case because mandatory profit sharing reduces wages and raises the workers' profit income, thereby mitigating excessive labour supply incentives.
Keywords: D62; J22; J33; 330